Case report: A 17-year-old male with primary pulmonary osteosarcoma - Wen, Xin; Xue, Liyan; Jiang, Xu; Jiang, Jiuming; Li, Meng; Zhang, Li (Frontiers in Medicine, 2024)
Primary pulmonary osteosarcoma is one of the extraskeletal osteosarcomas originating from the lung with an extremely low incidence and highly invasive potential. Here we report a case of primary pulmonary osteosarcoma treated in our hospital with a literature review. The patient, a 17-year-old male, had a cough and hemoptysis for 20 days. Computed tomography (CT) and positron emission tomography (PET) /CT were performed in our hospital. According to pathological examination after surgery, the tumor was diagnosed as a high-grade sarcoma with remarkable osteogenesis and necrosis. Based on radiological and histological examinations, a diagnosis of primary pulmonary osteosarcoma originating was considered. The patient underwent surgery and adjuvant chemotherapy. This patient has been under consecutive follow-up for nearly 8 years, showing no signs of recurrence or distant metastasis. Primary pulmonary osteosarcoma is a rare lung malignancy that shows rapid progression, nonspecific symptoms and inapparent signs at an early stage. The diagnosis of primary pulmonary osteosarcoma highly relies on imaging and histological examinations, among which chest CT is the predominant method to check this disease.